Behavioral Counseling of Theory of Planned Behavior-Based to Increase Tuberculosis Patients` Obedience in Medication Nutrition, and Prevention of Transmission: Randomized Control Trial - Novian Mahayu Adiutama; Wardah Fauziah (Journal Of Nursing Practice, 2022)
Background: Adherence behavior of tuberculosis patients become the most crucial factor in achieving success treatment, including adherence to compliance with medication, prevention of transmission, and nutritional compliance. Purpose: This study aims to determine the effect of behavioral counseling based on Theory of Planned Behavior (TPB) in improving adherence of TB patient. Methods: Quasy-experiment pre-post-test with control group were conducted on 108 patients with pulmonary tuberculosis at a Puskesmas located in Subang with simple random sampling technique. This study was conducted by behavioral counseling of TPB-Based in the treatment groups for 2 months. The statistical test used was the independent t test and chi-square. Results: There were significant differences (p<0,05) between treatment and control groups on attitude toward behavioral variables (ATB), subjective norm (SN), perceived behavior control (PBC), intention, medical adherence, prevention of transmission and nutritional compliance. Conclusion: There were significant differences (p<0,05) between treatment and control groups on attitude toward behavioral variables (ATB), subjective norm (SN), perceived behavior control (PBC), intention, medical adherence, prevention of transmission and nutritional compliance. Behavioral counseling of TPB-Based proven to have an effect in improving the ATB, SN, PBC, intention, medical adherence, prevention of transmission, and nutrition compliance of TB patients.